2021
DOI: 10.3390/jcm10143046
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Minor and Major Depression through Voice as a Biomarker Using Machine Learning

Abstract: Both minor and major depression have high prevalence and are important causes of social burden worldwide; however, there is still no objective indicator to detect minor depression. This study aimed to examine if voice could be used as a biomarker to detect minor and major depression. Ninety-three subjects were classified into three groups: the not depressed group (n = 33), the minor depressive episode group (n = 26), and the major depressive episode group (n = 34), based on current depressive status as a dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Shin et al ( 37 ) used machine learning on data extracted from semistructured interview recordings. Previous research showed that depressed patients had simpler, lifeless voices with lower volume.…”
Section: Resultsmentioning
confidence: 99%
“…Shin et al ( 37 ) used machine learning on data extracted from semistructured interview recordings. Previous research showed that depressed patients had simpler, lifeless voices with lower volume.…”
Section: Resultsmentioning
confidence: 99%
“…Voice recordings are closer to real life, allowing for automated quantitative analysis of voices in the future. The interview also allowed the voice to be recorded for a sufficient period (>15 minutes), unlike most previous studies that used audio recordings ranging from a few seconds to several minutes in length [23][24][25], and permitted the inclusion of colloquial and paralinguistic expressions that are informative for speech analysis [15,17]. In a recent study using the Emofilm database, which is a collection of short clips of movies in several languages, Costantini et al [18] explored and concluded that a cross-language classifier maintains a Thigh performance despite variations in languages and cultures.…”
Section: Strengthsmentioning
confidence: 99%
“…By overcoming subjectivity, various attempts have been made to detect and address depression and suicidal ideation. Studies have been conducted to identify depression based on the fact that people with depression exhibit greater hesitation in their voice and a monotonous tone ( 13 ). Studies are also underway that aim to predict depression and suicide risk by clustering texts published on social media ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%